The new production of knowledge: The dynamics of science and research in contemporary societies - Gibbons, Michael; Limoges, Camille; Nowotny, Helga; Schwartzman, Simon; Scott, Peter (Sage Publications, 1994)
In this provocative and broad-ranging work, the authors argue that the ways in which knowledge - scientific, social and cultural - is produced are undergoing fundamental changes at the end of the twentieth century. They claim that these changes mark a distinct shift into a new mode of knowledge production which is replacing or reforming established institutions, disciplines, practices and policies. Identifying features of the new mode of knowledge production - reflexivity, transdisciplinarity, heterogeneity - the authors show how these features connect with the changing role of knowledge in social relations. While the knowledge produced by research and development in science and technology is accorded central concern, the authors also outline the changing dimensions of social scientific and humanities knowledge and the relations between the production of knowledge and its dissemination through education.